Optimizing Junior High School Students' Mathematical Literacy through Wordwall-Based E-Modules with the FICAS Learning Model - Wijayanto, Zainnur; Rochmiyati, Siti; Hidayat, Rosidah Aliim; Trisnawati, Desi (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
The  development of digital technology opens up great opportunities in the transformation of mathematics learning, especially in improving students' mathematical literacy. This study aims to develop a Wordwall-based e-module integrated with the FICAS (Flipped Classroom–Advocacy Sosiograph) learning model that is valid, useful, and can help junior high school students become more independent and more mathematically literate learners. The development study of the design research type, which includes the analysis, design, expert validation, limited trials, and assessment phases, is the methodology used. Teachers need to understand the use of technology in learning, especially through wordwall-based e-modules. The technique analysis used is T test analysis to compare the use of wordwall-based e-modules.   The findings of this study reveal that the Wordwall-based e-module is able to optimize the flipped classroom approach interactively, improve conceptual understanding, student interest in mathematics learning, and encourage mathematical literacy skills more meaningfully. These findings indicate that the integration of digital media and innovative learning models has significant potential in supporting 21st-century mathematics learning.